IET Conference on Railway Traction Systems (RTS 2010) 2010
DOI: 10.1049/ic.2010.0041
|View full text |Cite
|
Sign up to set email alerts
|

Energy saving by using regenerating braking as normal train operation

Abstract: Two boosterless electrification systems have been designed and modelled using Mott MacDonald's in-house multi-train simulator TRAIN to assess the benefits from energy savings through the use of regenerative braking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The TPC model covers the movement modelling of each train given in the forecasted or current timetable. The train movement parameters could be determined by (1) according to the Newton's second law of motion.…”
Section: Model Of the Electrified Railway Line (Erl)mentioning
confidence: 99%
See 1 more Smart Citation
“…The TPC model covers the movement modelling of each train given in the forecasted or current timetable. The train movement parameters could be determined by (1) according to the Newton's second law of motion.…”
Section: Model Of the Electrified Railway Line (Erl)mentioning
confidence: 99%
“…Meanwhile due to the rolling stock modernization the and replacing programs in perspective of the next years the absolute majority of the rolling stock is going to be equipped with regenerative braking. That condition gives the opportunity of braking power utilization, which in the case of a large number of stops enables to save between 10 % and 30 % of traction energy [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the traction energy used to drive the rail vehicles accounts for the majority of the total energy consumption in rail transport systems [2], [3]. Regenerative braking of the traction electric motors converts the kinetic energy into the electrical energy for reuse and thus improve the energy efficiency.…”
Section: Introductionmentioning
confidence: 99%